2001
DOI: 10.1161/hq1201.100227
|View full text |Cite
|
Sign up to set email alerts
|

Mast Cell Chymase Inhibits Smooth Muscle Cell Growth and Collagen Expression In Vitro

Abstract: Abstract-In the vulnerable areas of fibrous caps of advanced atherosclerotic lesions, chymase-containing mast cells are present. In such areas, the numbers of smooth muscle cells (SMCs) and the content of collagen are reduced. In this in vitro study, we found that the addition of chymase, isolated and purified from rat serosal mast cells, to cultured rat aortic SMCs of the synthetic phenotype (s-SMCs) inhibited their proliferation by blocking the G 0 /G 1 3 S transition in the cell cycle. Rat chymase and recom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
45
0

Year Published

2002
2002
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(46 citation statements)
references
References 36 publications
1
45
0
Order By: Relevance
“…Our data and those reported by others (51) suggest that chymase inhibits the growth of human airway and vascular smooth muscle cells in vitro due to effects on matrix structure and to activation of TGF-␤. In contrast, in vivo data suggest that transgenic overexpression of a rat chymase in vascular smooth muscle promotes cell proliferation, possibly through production of angiotensin II (52).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Our data and those reported by others (51) suggest that chymase inhibits the growth of human airway and vascular smooth muscle cells in vitro due to effects on matrix structure and to activation of TGF-␤. In contrast, in vivo data suggest that transgenic overexpression of a rat chymase in vascular smooth muscle promotes cell proliferation, possibly through production of angiotensin II (52).…”
Section: Discussionsupporting
confidence: 87%
“…In some systems CD44 has been shown to act as a docking site for proteolytically active MMP-9 (57); immobilized active MMP-9 then cleaves latent TGF-␤ to its active form (58). Interestingly, while mast cell-derived chymase has been shown to release latent TGF-␤ from epithelial cell cultures (59), it has a variable ability to activate latent TGF-␤ directly (51,59,60). One could speculate that local release of chymase by mast cells, and potentially by ASM cells (61), activates MMP-9 and induces the release of latent TGF-␤, which, in turn, is activated by either MMP-9 or chymase.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, tryptase is involved in tissue fibrosis, and chymase induces apoptosis of cells with relatively low differentiation, including vascular smooth muscle cells, bronchial smooth muscle cells, and cardiomyocytes [16][17][18][19][20]. In other words, if we presume that there are undifferentiated cells in the fovea, then with regard to the action of these serine proteases, idiopathic epiretinal membranes may develop when tryptase activity is predominant, and idiopathic macular holes may develop when chymase activity is predominant.…”
Section: Discussionmentioning
confidence: 99%
“…Shiota et al (21) reported that RMCP I mRNA expression in SHR hearts was significantly higher than in WKY rat hearts. RMCP I may be involved in cardiovascular remodeling via the degradation of fibronectin (22,23) and by the activation of transforming growth factor-β (24,25). On the other hand, RMCP II may contribute to an increase of vascular permeability (26).…”
Section: Fig 4 Angiotensin I-induced Vasoconstrictions In Isolated mentioning
confidence: 99%